SMALL BUSINESS PERFORMANCE REVIEW FROM DIGITAL MARKETING LITERATURE AND INNOVATIVE THINKING PATTERNS THROUGH THE INTERVENING VARIABLES OF SMALL BUSINESS COMPETITIVENESS - Suheli Suheli; Furtasan Ali Yusuf; Budi Ilham Maliki (Yayasan Education and Social Center, 2023)
This research aims to develop small business innovation during a global crisis and to design a digital business economy. The purpose of this research is to create a digital business economy. The research method is a survey method that involves distributing questionnaires to 225 small businesses in the province of Banten. For the analysis, structural equation modeling (SEM) tools use. Researchers disseminated questionnaires based on various indicators, including 11 indicators of small business performance, 14 indicators of competitiveness, 16 indicators of digital marketing, and eight indicators of innovation thinking. Digital Marketing Literacy and Innovative Thinking on Small Business Competitiveness are at 0.027 and 0.000<0.05. On the other hand, digital marketing literacy and Innovative Thinking on Small Business Performance are at 0.000, and 0.010 < 0.05 (not significant), and Small Business Competitiveness to Small Business Performance is 0.003. the significance of the mediation shows that the mediation of Small Business Competitiveness in digital marketing literacy, Innovative Thinking Patterns is at 1.54 and 2.06 > 1.96. Limitations of the research, The researcher restricts the scope of the survey only to cover small businesses and has yet to begin investigating the issue of medium-sized enterprises in the province of Banten